Demography and climate change. The growing number of people and its consequences for ecology, social redistribution systems and urban living. - (:unkn) unknown (My University, 2015)
A growing population is good for social redistribution systems, but bad for the climate. Beyond this simple statement, demography, economic development, resource usage, climate change and political interventions influencing migration, fertility and social redistribution are not so easily brought together in a way to fully acknowledge for their interdependency. This book takes up the associated methodlogical challenges that are mirrored by several paradoxes: On the one hand, the reduciton of western socieites`ecological footprint is well supported by declining birth rates. On the other hand, sustainable transport, wast of sewage systems call either for population growth or a stronoger urbanization of a declining population to remain affordable. At the same time, theris the argument of population growth being necessary to finance the welfare state, its pension systemss as elderly care. As both "solutions" to demographic decline - increased migration and pro-natalist family policies - are politically heavily disputed, and given the interdependencies of poulation growth, climate change and resource availablity, this collection of articles shows, that an expert discussion on these aspects should indeed include the necessary normative aspects associated with the questions of influencing population size by policies. This book contains the inputs of international high profile researchers, discussing how these issues will shape the socio-economic reality in the middle of the century
Keywords: Bevölkerungsentwicklung; Ökologie; Umweltschutz; Klimawandel; Bevölkerungswachstum; Ressourcenverbrauch